2016
DOI: 10.1097/mjt.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol for Oral Mucositis Prevention in Patients With Fanconi Anemia Undergoing Hematopoietic SCT: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: Fanconi anemia is a rare inherited aplastic anemia, which is cured only by hematopoietic stem-cell transplantation (HSCT). One of the most debilitating complications of high-dose chemotherapy regimen before HSCT is oral mucositis (OM), which occurs frequently in this population. Vitamin D has identified immunoregulatory, anti-inflammatory, and antioxidant role. This study was designed to examine the efficacy of vitamin D in the prevention of OM in patients with Fanconi anemia undergoing allogenic HSCT. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Calcitriol, also called 1,25-dihydroxycholecalciferol, is the active metabolite of vitamin D. Vitamin D is a group of fatsoluble hormones responsible for increasing intestinal absorption of calcium, magnesium, and phosphate [73]. Vitamin D is speculated to have anti-inflammatory properties related to its ability to diminish the release of TNF-α and to increase the synthesis of interleukin10 [71]. Table 5 summarizes the details of studies reviewed on calcitriol.…”
Section: Calcitriolmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcitriol, also called 1,25-dihydroxycholecalciferol, is the active metabolite of vitamin D. Vitamin D is a group of fatsoluble hormones responsible for increasing intestinal absorption of calcium, magnesium, and phosphate [73]. Vitamin D is speculated to have anti-inflammatory properties related to its ability to diminish the release of TNF-α and to increase the synthesis of interleukin10 [71]. Table 5 summarizes the details of studies reviewed on calcitriol.…”
Section: Calcitriolmentioning
confidence: 99%
“…The use of calcitriol for prevention of OM in patients undergoing HSCT was evaluated in a single RCT [71]. Twentyeight patients with Fanconi anemia undergoing HSCT were treated with either oral calcitriol or placebo.…”
Section: Gcalcitriol (Po): Hsct-prevention Guideline: No Guideline Pomentioning
confidence: 99%
“…Another study with smaller patient cohort size (n=14) found no significant benefit. 24 Therefore collectively, these data argue for a beneficial role for Vit D in improving treatment-associated mucositis in cancers and perhaps hematopoietic stem cell transplantation. 25 IL-22 is an important cytokine in gut homeostasis.…”
Section: Discussionmentioning
confidence: 98%
“…Data from a study by Anand et al (2017) with adult oral cancer patients revealed that vitamin D supplementation significantly improved treatment-associated mucositis [23]. Another study with smaller patient cohort size (n = 14) found no significant benefit [24]. Therefore collectively, these data argue for a beneficial role for vitamin D in improving treatment-associated mucositis in cancers and perhaps hematopoietic stem cell transplantation [25].…”
Section: Discussionmentioning
confidence: 99%